Paradox of humanitarian intervention: A critical analysis of theory and practice - Tadelech Bubamo Welde; Baiq L. S. W. Wardhani (Masyarakat, Kebudayaan dan Politik, 2020)
Since the end of the Cold War, thoughtlessness act in conducting ‘humanitarian interventions’ has posed analytical challenges for international relations academicians. Traditional security advocators have tried to distinguished implications of ‘humanitarianism’ based on their interest and how it helps state in regaining the outcome. This research identified motivation of state in conducting humanitarian intervention. There are growing studies, as expressed by the constructivist, that humanitarianism is states’ political weapon that shifted the involvement patterns of policymakers and actors in humanitarian interventions. On the other hand, primary criticism from realism stressed economic and political ambition behind humanitarian interventions and makes it impossible to be moral, ethical, and cosmopolitan. The objective of this study is to examine the practices, motives, and challenges of humanitarian interventions. Data gathered from published books and journals selected through rigorous analysis. The research finds that the failure of humanitarian interventions indicates the following: First, humanitarian interventions requires expensive cost in people’s life and other resources. Moreover, there is a moral obligation to save the victims.  Second, actors are engaged to operate the mission and has limited right to demonstrate their self-interest to protect the victims. Third is the issue of sovereignty and the subjected state’s willingness to integrate. To overcome the problem, government should promote global governance transformation and the cosmopolitanism nature between actors.